Explaining the experience of prenatal care and investigating the association between psychological factors with self-care in pregnant women during COVID-19 pandemic: a mixed method study protocol - Marzieh Masjoudi; Armin Aslani; Somayyeh Khazaeian; Azita Fathnezhad-Kazemi (BMC, 2020)
Abstract Background Coronavirus disease 2019 (COVID-19) is a novel global public health emergency. Prenatal care (PNC) providing institutes should identify the needs and demands of pregnant women by optimizing the means of PNC services during the COVID-19 pandemic. The present study aims to: a) explain prenatal care experiences; b) assess the factors affecting self-care, and c) present a prenatal care guideline and Strategies to improve the PNC. Methods This mixed-methods study with a sequential explanatory design consists of three phases. The first phase is a qualitative study exploring the prenatal care experiences among pregnant women. In this phase, the subjects will be selected through purposive sampling; moreover, in-depth individual interviewing will be used for data collection. Finally, the conventional content analysis approach will be employed for data analysis. The second phase is quantitative and will be used as a cross-sectional approach for assessing the association between psychological factors of self-care. In this regard, a multistage cluster sampling method will be used to select 215 subjects who will be visited in health care centers of Tabriz, Iran. The third phase will be focusing on developing a prenatal care guideline and Strategies, using the qualitative and quantitative results of the previous phases, a review of the related literature, and the nominal group technique will be performed among experts. Discussion The present research is the first study to investigate the prenatal care experiences and factors influencing self-care among pregnant women during COVID-19 pandemic. For the purposes of the study, a mixed-methods approach will be used which aims to develop strategies for improving health care services. It is hoped that the strategy proposed in the current study could lead to improvements in this regard. Ethical code IR.TBZMED.REC.1399.003.